Analisis Current Ratio Dan Best To Equity Ratio Terhadap Return On Equity Pada Perusahaan Farmasi - Aulia Zahra; Diah Yudhawati; Hurryaturrohman (Journal of Business Economics and Management | E-ISSN : 3063-8968, 2025)
This research aims to determine the effect of Current Ratio and Debt to Equity Ratio on Return On Equity in pharmaceutical sub-sector companies listed on the Indonesia Stock Exchange for the 2019-2023 period. The analysis method in this study uses panel data regression analysis, descriptive analysis, classical assumption testing, multiple linear regression, hypothesis testing, and the coefficient of determination. The population of this study is pharmaceutical companies listed on the Indonesia Stock Exchange for the 2019-2023 period, and the sample in this study consists of 6 companies that have met the sample selection criteria using the purposive sampling method. The results showed that partially (t-test), the Current Ratio has an effect on Return On Equity, the Debt to Equity Ratio has an effect on Return On Equity, and the results showed that simultaneously (F-test) or together, the Current Ratio and Debt to Equity Ratio have an effect on Return On Equity in Pharmaceutical Companies listed on the Indonesia Stock Exchange for the 2019- 2023 period.